Prevalence of prescribing errors in Farmasi Klinik Pakar, Hospital Raja Perempuan Zainab II - Ahmad, Muhammad Nazmi; Zahari, Siti Suzilawani; Muhammed, Khalilah; Ibrahim, Nour Izyanhazwani (2009)
Prescribing errors may be defined as the incorrect drug selection for a patient. Such errors can include the dose, quantity, indication, or prescribing of a contraindicated drug. Lack of knowledge of the prescribed drug, its recommended dose, and of the patient details contribute to prescribing errors. Objectives of our study are to identify the characteristics and to quantify rate and frequency of prescribing errors in 'Farmasi Klinik Pakar', HRPZ II. The obtained results also will be used to evaluate frequency of errors for each department. This study also aimed to measure the frequency of prescribing errors in 'Farmasi Klinik Pakar' of HRPZ II from I st January 2008 till 30th June 2008. This is a retrospective study over six months period. All of the prescriptions from the 'Farmasi Klinik Pakar' of Hospital Raja Perempuan Zainab II dated from I January 2008 until 30 June 2008 was reviewed. The prescriptions with errors which already identified by the pharmacists were analyzed using SPSS Version 16.0 further to determine the characteristic and frequency of the errors. Prescriptions with errors were recorded in the form according to their errors, month and department respectively. The groups of errors are inappropriate regimen, incomplete prescription, inappropriate prescription and miscellaneous. Each main groups are divided into a sub group and (as in appendixes) were reviewed. A number of 476 (0.8%) prescriptions have errors from total of the prescriptions that have been reviewed. Majority of errors were made by Medical Department. In inappropriate regimen cases, 'wrong dose' recorded 35.l % error, while 'wrong frequency' and 'wrong duration' were 19.9% and 1.7% respectively. Errors on incomplete prescription cases showed 'no duration' were 10.9%, followed by 'no dose' (6.2%), 'no frequency' (5.8%),'no patient data' (4.1%) and 'no Doctors' chop & signature' (3.0%). While, incomplete prescription which consist of 'poly-pharmacy' and 'drug interaction' recorded 0.2% & 0.6% of errors for both of this error. For miscellaneous cases, unclear handwriting and not in MOH were 6.4% and 13. 7% respectively. The lowest of prescribing errors for miscellaneous case were authenticity of prescriber & prescription which recorded (0.2%).